Autoinducer-2 promotes adherence of Aeromonas veronii through facilitating the expression of MSHA type IV pili genes mediated by c-di-GMP - Li, Yi (2024)
Aeromonas veronii can adhere to host cells through different adherence factors including outer-membrane proteins (OMPs), lipopolysaccharide (LPS), and pili, but its adherence mechanisms are still unclear. Here, we evaluated the effect of autoinducer-2 (AI-2) on adherence of A. veronii and its regulation mechanism. After determination of the promotion effect of AI-2 on adherence, we investigated which adherence factor was regulated by AI-2, and the results show that AI-2 only limits the formation of pili. Among the four distinct pili systems, only the mannose-sensitive hemagglutinin (MSHA) type IV pili genes were significantly downregulated after deficiency of AI-2. MshE, an ATPase belonged to MSHA type IV pilin, was confirmed as c-di-GMP receptor, that can bind with c-di-GMP which is positively regulated by AI-2, and the increase of c-di-GMP can promote the expression of MSHA type IV pili genes and adherence of A. veronii. Therefore, this study confirms that c-di-GMP positively regulated by AI-2 binds with MshE, then increases the expression of MSHA pili genes, finally promoting adherence of A. veronii, suggesting a multilevel positive regulatory adhesion mechanism that is responsible for A. veronii adherence.